FORMATION OF PAIRS AND GROUP TO IMPROVE ENGLISH LANGUAGE SKILLS OF GRADE VI STUDENTS OF ELEMENTARY SCHOOL 060878 - Eva Betty Simanjuntak; Dea Yuanita Nasution; Hiskia Rahmadani; Joy Gracia Pakpahan; Rizka Amelia; Winda Nainggolan (PT. Jurnal Center Indonesia Publisher, 2025)
This study aims to evaluate the effectiveness of group learning methods in improving the English skills of sixth-grade students at SD Negeri 060878. Using a qualitative approach involving direct interviews, questionnaires, and documentation, this study identified three main problems that hinder the success of group learning: gender differences affecting group formation, difficulty ensuring the active participation of each member, and relatively long time for group management. The results of the study indicate that these problems cause group learning to be less effective and have an impact on the decline in students' English skills. Therefore, strategies such as forming inclusive groups, clear division of tasks, the use of participatory observation instruments, the utilization of technology, and the implementation of the Problem-Based Learning approach are recommended to improve the effectiveness of group learning and students' English skills. This study provides an important contribution to developing English teaching methods at the elementary school level by considering social aspects and more effective classroom management.